The effect of quercetin on adipogenesis, lipolysis, and apoptosis in 3T3‐L1 adipocytes: The role of SIRT1 pathways - Mohammad Hasan Maleki; Sara Abdizadeh Javazm; Sanaz Dastghaib; Anahita Panji; Mohammad Hojjati Far; Hajar Mahmoodi; Morvarid Siri; Sayed Mohammad Shafiee (Wiley, 2024)
Abstract Background Lipotoxicity, caused by adipocyte triglyceride over‐accumulation, contributes to obesity‐related comorbidities such as hypertension, type 2 diabetes, coronary heart disease, respiratory dysfunction, and osteoarthritis. This study focuses on determining how sirtuin‐1 (SIRT‐1) mediates quercetin's (QCT) effect on 3T3‐L1 adipocytes. Key aspects of this study include preventing adipogenesis, inducing lipolysis, and stimulating adipocyte apoptosis. Methods 3T3‐L1 adipocytes underwent treatment with varying QCT doses, lipopolysaccharide (LPS), and the SIRT‐1 inhibitor EX‐527, followed by 3‐(4,5‐dimethylthiazol‐2‐yl)‐2,5‐diphenyl‐2H‐tetrazolium bromide [MTT] assay for cell viability assessment. Furthermore, quantitative real‐time polymerase chain reaction measured mRNA expression levels of adipogenesis markers (fatty acid synthase [FASN] and peroxisome proliferator‐activated receptor gamma [PPARγ]), lipolysis markers (adipose triglyceride lipase [ATGL] and hormone‐sensitive lipase [HSL]), and apoptosis markers (B‐cell lymphoma2 [Bcl‐2], Bcl‐2 Associated ‐X‐protein [BAX] and Caspase‐3). Results The data showed that LPS + QCT significantly reduced cell viability in a dose‐ and time‐dependent manner, unaffected by LPS + QCT + EX‐527. Treatment with LPS + QCT did not affect FASN and PPARγ expression but significantly increased ATGL and HSL mRNA expression compared with LPS alone. Interestingly, EX‐527 reversed the effects of LPS + QCT on lipogenesis and lipolysis markers completely. QCT enhanced apoptosis in a SIRT‐1 independent pattern. Conclusion The data suggest that QCT suppresses adipogenesis while increasing lipolysis via SIRT‐1. However, QCT's effects on apoptosis appear to be independent of SIRT‐1. These findings provide further evidence for QCT's effects on adipocytes, particularly its interaction with SIRT‐1.